Four new species of the genus Mallinella (Araneae: Zodariidae) from Malaysia - Zhang, Bao-Shi; Zhang, Feng (Zootaxa, 2019)
Four new species of the genus Mallinella Strand, 1906, from the natural forests of Malaysia, are described as Mallinella bicanaliculata sp. n. (♂♀), M. calautica sp. n. (♂♀), M. laxa sp. n. (♂♀), and M. obliqua sp. n. (♂♀). The four new species belong to four species groups and were collected from the forest litter in Sabah state by sieving.